Construction of Ag/AgCl@MIL-53(Fe): Achieving Efficient Photocatalytic Water Oxidation via the Plasma-Phase Silver and Heterojunction Synergistic Effect - Liu, Xiaofei; Bekchanov, D.; Baikenov, M.I.; Su, Xintai (Eurasian Journal of Chemistry, 2024)
The development of highly efficient water oxidation catalysts is a bottleneck in achieving artificial photosyn-thesis, as water oxidation is a complex process involving multiple electron and proton transfers. To further improve the photocatalytic water oxidation performance of MIL-53(Fe), a series of Ag/AgCl@MIL-53(Fe) samples with different Fe:Ag ratios were synthesized by hydrothermal methods and used in the photocatalytic water oxidation reactions. XRD characterization showed the successful preparation of Ag/AgCl@MIL-53(Fe) heterostructure catalysts. The reaction results showed that sample AAM-2 (Fe:Ag=5:1) had the best photo-catalytic water oxidation performance, with the highest TOF value of 0.14 mmol/(g·s) and quantum efficien-cy of 39.0 % under the conditions of catalyst mass of 1 mg and pH=9.0 for boric acid-borax buffer solution. Measurements of photocurrent indicated that the AAM-2 samples doped with Ag/AgCl had higher photocur-rent densities, thus improving the photocatalytic performance. This provides new insights for constructing highly efficient porous MOFs catalysts.
Keywords: Metal organic framework (MOFs); hydrothermal method; MIL-53(Fe); Ag/AgCl@MIL 53(Fe); surface plasma resonance; heterojunction; photocatalysis of water oxidation; photocurrent densities